Non-Appearance before the International Court of Justice and the Role and Function of Judges ad hoc (2017)
An endless discussion has taken place regarding the role and function of judges ad hoc in contemporary international adjudication. In this regard, doctrine has been important through its ample contribution to the understanding of the institution of the judge ad hoc and its role and function. In fact, from these contributions it is possible to affirm the relevance of the judge ad hoc in contemporary international adjudication. Nonetheless, all these aspects have been analysed having in mind cases where both parties take part in the proceedings. Consequently, a question arises as to what is the role and function of a judge ad hoc when the appointing state fails to defend its case. This article seeks therefore to analyse the role and function of judges ad hoc in cases of partial non-Appearance before the International Court of Justice. © Sarmiento and Arevalo, 2018.